In vitro modulatory effects of microglia on neuroepithelial cell neurodifferentiation - Tong, Chih Kong (2017)
Neural precursor cells (NPC) give rise to neurons and glial cells during embryonic brain development. Dysregulation of NPC growth and function can cause brain deformities and result in psychiatric and behavioural deficits later in life. Recent discoveries reveal that microglia are involved in modulating neurogenesis during embryonic brain development. This study explores the role of microglia in regulating NPC proliferation and neural differentiation using an in vitro cell culture approach. For this, BV2 microglia-conditioned media from cultures treated acutely and chronically with 1μg/ml lipopolysaccharide were collected and incubated with the NE-4C neuroepithelial cell line. NE-4C cultures were either non-induced or induced into neural differentiation using a retinoid analogue, EC23. The effects of microglia on NPC were elucidated by examining proliferation, cell death, pluripotency and cell adhesion markers, as well as early and terminal neural differentiation. Firstly, it was shown that BV2 soluble factors, regardless of activation status, significantly reduced the proliferation of NE-4C cells at all time points examined (from 24 to 96 hours). For instance, at 24 hours, unstimulated BV2-conditioned media reduced non-induced NE-4C proliferation by 83.00 ± 4.43% (p<0.001). DAPI/PI staining and Annexin-V/PI assays showed no increase in apoptotic cells in the presence of BV2 microglia-conditioned media, confirming that the reduced proliferation of NE-4C is unrelated to apoptosis. By immunophenotyping and RT-qPCR analysis, it was shown that BV2 microglia-conditioned media does not alter the expression of pluripotency markers (SSEA-1 and CD133) and neural commitment and maintenance factors (HES1, HES3, HES5, MASH1, SOX1, NGN2, and PAX6) in NE-4C neuroepithelial cells at the early phase of neural differentiation. Immunocytochemical studies showed that BV2 microglia-conditioned media inhibited the production of RC2+ radial glial cell and TUJ1+ neurons during the early phase of neural differentiation. This was accompanied by the reduced formation of neural aggregates. Next, western blot studies showed that BV2 microglia-conditioned media up-regulate the expression of E-cadherin, beta-catenin, and CDC42 but down-regulate the expression of N-cadherin in NE-4C cells. The alteration of the expression of these molecules in NPC may arrest the cells in an undifferentiated state and therefore fail to commit into neural differentiation. Subsequently, the present study elucidated whether microglia-derived soluble factors can impact the terminal production of neuronal cells. The results demonstrate that unstimulated BV2 microglia-conditioned media reduced TUJ1+ neuron production in EC23-induced NE-4C cultures by 58.6% (p<0.001). However, there were no significant changes in the percentage of GFAP+ astrocytes. BV2-conditioned media also did not affect the expression of the mature neuron marker MAP2 and synapse marker SYT1 in NE-4C derived neurons. This study then evaluated the effects of BV2-conditioned media on neurite complexity. BV2-conditioned media significantly reduced the number of neurites from 9169 ± 1735 in untreated cultures to 1362 ± 117.6 (p<0.001). Total neurite length was also significantly decreased from 5246 ± 924.7px in untreated cultures to 1026 ± 203.6px (p<0.001). Neurite attachment points were also reduced from 3115 ± 451.5 in untreated cultures to 1310 ± 356.8 (p<0.001). Also, the number of neurite end points were significantly reduced from 7776 ± 1845 in untreated cultures to 4060 ± 952.1 (p<0.001). There was no neural differentiation observed in non-induced NE-4C cultures suggesting that BV2 soluble factors do not contribute to the initiation of neurogenesis. Also, the activation status of microglia had no effect on NE-4C neural differentiation in any of the parameters examined, indicating that ubiquitous microglial soluble factors are responsible for the effects described here. To conclude, the primary finding of this study is that microglia exert inhibitory effects on the neural differentiation of NPC.